Complex mortgages - Gene Amromin; Jennifer Huang; Clemens Sialm; Edward Zhong (Federal Reserve Bank of Chicago, 2010)
Complex mortgages became a popular borrowing instrument during the bullish housing market of the early 2000s but vanished rapidly during the subsequent downturn. These non-traditional loans (interest only, negative amortization, and teaser mortgages) enable households to postpone loan repayment compared to traditional mortgages and hence relax borrowing constraints. At the same time, they increase household leverage and heighten dependence on mortgage refinancing to escape changes in contract terms. We document that complex mortgages were chosen by prime borrowers with high income levels seeking to purchase expensive houses relative to their incomes. Borrowers with complex mortgages experience substantially higher ex post default rates than borrowers with traditional mortgages with similar characteristics.
Keywords: 330; Finanzmarkt; Kreditmarkt; Hypothek; Verschuldungsrestriktion; USA